Influência da quantidade de floresta sobre a ocorrência de mamíferos carnívoros na Mata Atlântica brasileira - Regolin, André Luis (2016)
Habitat fragmentation process is the main threat to the conservation of terrestrial mammals at the global level. Despite the importance of understanding the degree which species are sensitive to the effects of habitat fragmentation, there are few studies that assess the relationship between tropical forest fragmentation and the occurrence of carnivore mammals. We investigated how landscape structure — forest amount, patch density, edge amount,perimeter-area ratio and spatial heterogeneity — affects the diversity of carnivore mammals at multiple extents within 22 Atlantic Forest landscapes. We hypothesized that (a) carnivore richness is positively related to forest amount;and (b) the occurrence of species will vary according to its sensitivity to forest loss and its preference for forest or open areas. Species richness and composition were correlated with several landscape structure metrics. Due to a high correlation among the metrics, we adopted forest amount as the principal predictor variable. Using the model selection method (AICc), we confirmed that forest amount positively influenced species richness, and we verified that the responses to landscape structure differed among species, possibly due to the differences in their habitat use. Our results reiterate the importance of protecting forest remnants to maintain the high quantity of forest within Neotropics, particularly where originally landscapes was covered by forests.